2017
DOI: 10.5530/jyp.2017.9.33
|View full text |Cite
|
Sign up to set email alerts
|

In-Silico Screening of Flavonoids targeted for Death Receptors in Cancer by Using Hex Molecular Docking

Abstract: Objective: Docking is one of the major tools in the drug development process, here we have selected certain flavonoid molecules such as Formononetin, Tangeritin, Myricetin and Kaempferol and we docked against Death Receptors (DRs) for the prevention of cancer progression. Materials and Methods: In this study, Protein Ligand Docking, we have used HEX as a Docking Software. Receptor structure was obtained from Protein Data Bank (PDB) while the ligand is drawn by using the Chem Draw Software and docking was done … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Despite the abundant evidence of formononetin-induced intrinsic apoptosis pathway, there is still no report on the apoptotic effect of formononetin mediated through the extrinsic pathways via stimulation of death receptors on the cell surface, such as tumor necrosis factor receptor (TNFR) superfamily. Nevertheless, a recent in silico study, which investigated the interactions between formononetin and death receptors, revealed that formononetin could be a potential molecule in inducing extrinsic apoptosis pathway (Vishnuvarthan et al, 2017). The study showed that formononetin displayed high affinity and steric compatibility to death receptor 5, which could be activated to mediate the TNF-related apoptosis-inducing ligand (TRAIL)-induced apoptosis (Walczak et al, 1997).…”
Section: Anticancer Molecular Targets and Mechanisms Of Formononetinmentioning
confidence: 99%
“…Despite the abundant evidence of formononetin-induced intrinsic apoptosis pathway, there is still no report on the apoptotic effect of formononetin mediated through the extrinsic pathways via stimulation of death receptors on the cell surface, such as tumor necrosis factor receptor (TNFR) superfamily. Nevertheless, a recent in silico study, which investigated the interactions between formononetin and death receptors, revealed that formononetin could be a potential molecule in inducing extrinsic apoptosis pathway (Vishnuvarthan et al, 2017). The study showed that formononetin displayed high affinity and steric compatibility to death receptor 5, which could be activated to mediate the TNF-related apoptosis-inducing ligand (TRAIL)-induced apoptosis (Walczak et al, 1997).…”
Section: Anticancer Molecular Targets and Mechanisms Of Formononetinmentioning
confidence: 99%
“…The MM/GBSA analysis of selected compound Pubchem ID 68077 has shown binding energy of 34.60. In recent study by Vishnuvarthan et al, 2017 reported that the in silico screening of flavonoids such as formononetin, tangeritin, myrecitin and kaempferol were used as targets against death receptors for prevention of cancer progression [38]. The Protein-ligand interactions of the stable docked HER alpha and tangeritin complex was visualized with ligand interaction diagram shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggested that these two molecules may act together increasing their potential. Another in silico study showed the affinity of some flavonoids to death receptors, including TNFR1 ( 37 ). Therefore, our data indicated that Mat-TMZ can initiate caspase cascade activation through the activation of the TNFR1 signaling pathway, leading to induction of both intrinsic and extrinsic apoptotic pathways.…”
Section: Discussionmentioning
confidence: 99%